Assessing the Accuracy of Common Clinical Tests for Detecting Palmaris Longus: A Prospective Study in a Tertiary Center - Jayachandiran, Anand Prasath; Rajendran, Suresh; U.S, Tanuja; Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Ananthappan, Manoj (Indian Journal of Plastic Surgery, 2023)
Background Palmaris longus (PL) is a short-bellied muscle with a long tendon that merges with the palmar aponeurosis. It is supplied by the median nerve and acts as a tensor of the palmar aponeurosis and flexes the wrist. This tendon is commonly used for tendon transfers and as a donor for tendon graft. There are numerous clinical tests to detect the presence of PL like Schaeffer's test, Thompson's test, Mishra's test I, Mishra's test II, Pushpakumar's “two-finger sign” method, and AIIMS test. The principle of all these tests is to make the tendon prominent by eliciting its flexor action and then its identification by inspection and palpation.Objectives The tests that are consistently easy to perform with good understandability would be easy to explain to the general population (patients). The aim of our study is to find out the accuracy and easy comprehensibility of various tests using compulsive postures for detecting PL tendon clinically.Materials and Methods This is a prospective study on 137 participants. All the patients were subjected to six clinical tests to detect the presence or absence of PL tendon. The results were recorded for both hands by a single observer.Results Of the 137 participants, 75 were males (54.74%) and 62 were females (45.26%). The mean age was 21 years. The AIIMS test showed the maximum number of tendons, that is, 113 (82.4%) in the right hand and 108 (78.8%) in the left hand. In view of the ability to comprehend the tests, 119 (86.9%) subjects understood Schaeffer's test very easily.Conclusion According to this study, the AIIMS test best demonstrates the PL tendon, and Schaeffer's test was the test most easily understood by the subjects.
Keywords: palmaris longus; Schaeffer's test; AIIMS test; Mishra's test; Thompson's test; Pushpakumar's “two-finger sign” method; tendon transfer